1992
DOI: 10.3758/bf03203584
|View full text |Cite
|
Sign up to set email alerts
|

Recording and analyzing eye-position data using a microcomputer workstation

Abstract: This paper presents a PC-based eye-position data collection and analysis system. Software routines are described that supplement hardware calibration procedures, improving data-collection accuracy and reducing the number of unusable trials. Collected eye-position data can be remapped over a displayed stimulus image and spatially and temporally represented by parameters such as individual fixations, clusters of fixations (Nodine, Carmody, & Kundel, 1978), cumulative clusters, and gaze durations. An important fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…It should be noted that in both the P+C and P conditions, detection was significantly lower for the outside than for the inside tumors, but as was noted previously, this was independent of whether or not a tumor had been reported in the inside zone. The lower detection rate probably had more to do with the fact that peripheral vision was required to detect the outside tumors (Nodine et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in both the P+C and P conditions, detection was significantly lower for the outside than for the inside tumors, but as was noted previously, this was independent of whether or not a tumor had been reported in the inside zone. The lower detection rate probably had more to do with the fact that peripheral vision was required to detect the outside tumors (Nodine et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…On the average, search was terminated after 5 sec. Eye position was recorded (Eye-Trac Model 210; Applied Science Laboratories, Waltham, MA) according to a limbus-reflection technique (see Nodine, Kundel, Toto, & Krupinski, 1992, for complete details of the eye-position recording and analysis procedures).…”
Section: Methodsmentioning
confidence: 99%
“…Methods of analysing the search pathways in medical images have been produced by Nodine and Kundel and Nodine at al. [28,29]. Nodine reported that the minimal dwell time for abnormality recognition of lung nodules is 900 ms and, with Kundel, provided a method to reduce the recognition failure of abnormal features [28].…”
Section: Discussionmentioning
confidence: 99%
“…True-negative decision dwell time is calculated from image regions that are lesion free but receive fixation clusters. 114 Higher display luminance, 115 calibration with the Digital Imaging and Communications in Medicine ͑DICOM͒ Grayscale Display Function standard, 116 high-performance monochrome rather than color display, 117 and 11-bit rather than 8-bit display 118 all result in higher search efficiency and improved diagnostic accuracy. Even the graphical user interface ͑GUI͒ and the way in which images and tool bars are positioned on the display can affect search efficiency.…”
Section: Evaluation Of Other Human Factors That Affect Diagnosticmentioning
confidence: 99%